Hypoxia/Hypercapnia‐Induced Adaptation Maintains Functional Capacity of Cord Blood Stem and Progenitor Cells at 4°C. Issue 12 (December 2014) - Vlaski, Marija; Negroni, Luc; Kovacevic‐Filipovic, Milica; Guibert, Christelle; de la Grange, Philippe Brunet; Rossignol, Rodrigue; Chevaleyre, Jean; Duchez, Pascale; Lafarge, Xavier; Praloran, Vincent; Schmitter, Jean‐Marie; Ivanovic, Zoran
<x xml:space="preserve">Abstract</x> We analyzed the effect of exposure to hypoxic/hypercapnic (HH) gas mixture (5% O2/9% CO2) on the maintenance of functional cord blood CD34+ hematopoietic stem and progenitor cells in severe hypothermia (4°C) employing the physiological and proteomic approaches. Ten‐day exposure to HH maintained the Day 0 (D‐0) level of hematopoietic stem cells as detected in vivo on the basis of hematopoietic repopulation of immunodeficient mice—short‐term scid repopulating cells (SRC). Conversely, in the atmospheric air (20% O2/0.05% CO2), usual condition used for cell storage at 4°C, stem cell activity was significantly decreased. Also, HH doubled the survival of CD34+ cells and committed progenitors (CFCs) with respect to the atmospheric air (60% vs. 30%, respectively). Improved cell maintenance in HH was associated with higher proportion of aldehyde dehydrogenase (ALDH) positive cells. Cell‐protective effects are associated with an improved maintenance of the plasma and mitochondrial membrane potential and with a conversion to the glycolytic energetic state. We also showed that HH decreased apoptosis, despite a sustained ROS production and a drop of ATP amount per viable cell. The proteomic study revealed that the global protein content was better preserved in HH. This analysis identified: (i) proteins sensitive or insensitive to hypothermia irrespective of the gas phase, and (ii) proteins related to the HH cell‐protective effect. Among them are some protein families known to be implicated in the prolonged survival of hibernating animals in hypothermia. These findings suggest a way to optimize short‐term cell conservation without freezing. J. Cell. Physiol. 229: 2153–2165, 2014. © 2014 Wiley Periodicals, Inc.